2015
DOI: 10.1108/medar-12-2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

The effect of national culture on the association between profitability and corporate social and environmental disclosure

Abstract: Research type: review Purpose: This paper aims to investigate the moderating effect of cultural dimensions (masculinity; individualism; and long term orientation) on the association between profitability and corporate social and environmental disclosure (CSED). Methodology: We apply the meta-analysis technique developed by Hunter, Schmidt and Jackson (1982) and Hunter and Schmidt (2000) for a sample of 48 published studies over the period of the last twenty years. Findings: We find that masculinity, individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 94 publications
(102 reference statements)
2
117
0
Order By: Relevance
“…The coefficient values in both models are significant at p <.05, thus supporting H 2 which hypothesises that culture influences CSR disclosure. This finding is similar to those found by Haniffa and Cooke (2005), Waldman et al (2006), Archambault and Archambault (2013), García-Sánchez et al (in press), Mohamed Adnan et al (2010), and Khlif et al (2015). The positive and significant effect of culture on CSR disclosure indicates that Malay-majority board members provide better CSR disclosure, supporting the view of Sendut (1991), Lim (1998), Rashid and Ibrahin (2008) and Zawawi (2008) the Malays are more oriented towards relationship building.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficient values in both models are significant at p <.05, thus supporting H 2 which hypothesises that culture influences CSR disclosure. This finding is similar to those found by Haniffa and Cooke (2005), Waldman et al (2006), Archambault and Archambault (2013), García-Sánchez et al (in press), Mohamed Adnan et al (2010), and Khlif et al (2015). The positive and significant effect of culture on CSR disclosure indicates that Malay-majority board members provide better CSR disclosure, supporting the view of Sendut (1991), Lim (1998), Rashid and Ibrahin (2008) and Zawawi (2008) the Malays are more oriented towards relationship building.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Prior studies by Archambault and Archambault (2003), García-Sánchez, Rodríguez-Ariza and Frías-Aceituno (2013), Waldman et al (2006), and Mohamed Adnan, Staden and Hay (2010) argued that culture could influence CSR (and voluntary) disclosure and decisionmaking process. Khlif, Hussainey, and Achek (2015) found that culture has a positive moderating effect on the relationship between profitability and environmental disclosure. Measuring specifically on the studies performed in Malaysia, Haniffa and Cooke (2005) found that Malay directors and Malay shareholders bring positive impacts to the company especially in terms of CSR disclosure.…”
Section: Theories and Hypothesis Developmentmentioning
confidence: 98%
“…The generators recognised the possible strategic implications of these changes on their cost, profits and competitiveness, consistent with Khlif et al (2015) and Maroun (2015), and most started to analyse CC risks and opportunities for planning and possible repositioning purposes. This is consistent with an anticipatory strategy.…”
Section: Period 2 -Anticipatory and Proactive Strategiesmentioning
confidence: 99%
“…Stakeholder theory suggests that companies try to manage their relationships with different stakeholders to gain competitive advantage, therefore lead to better financial performance (Khlif et al 2015). In response to pressures from various stakeholders such as governments, environmental groups, employees and the public, companies increase corporate social responsible reporting.…”
Section: Theorymentioning
confidence: 99%
“…Roberts' (1992) study confirms that the levels of corporate social responsible reporting are significantly influenced by stakeholder power, strategic posture and economic performance. Corporate financial profitability is a key factor that influences corporate social responsible reporting, but Khlif, Hussainey and Achek (2015) found that national culture moderates the association between profitability and corporate social responsible reporting. De Villiers and Alexander (2014) found evidence that management intent or company social and environmental performances do not necessarily drive corporate social responsible reporting but is rather a reflection of global corporate social responsible reporting templates.…”
Section: Introductionmentioning
confidence: 99%